Controle de qualidade físico-químico e biológico de extratos secos da casca do fruto de romã (Punica granatum L.) comercializados em farmácias magistrais - Juliana Machado Brêtas (2018)
Punica granatum L., popularly known as romã or pomegranate, originates in Asia, being cultivated in several subtropical and tropical regions around the world. Consolidated in traditional medicine with antibacterial, vermifuge, astringent action, among others, the demand for this plant and derived products has grown significantly in recent years, due to the greater knowledge of the therapeutic properties and the ease of acquisition of derivatives, such as the fruit peel dried extracts (FDEs). The most used part in therapeutics, including the production of FDEs, is the pericarp, which is rich in phenolic compounds such as punicalagin and ellagic acid. Variations in the levels of these active markers may have a direct impact on biological activities, so that the quality control of the FDEs is essential to ensure the authenticity and absence of adulteration by the addition of ellagic acid or other substances. In this way, the objective was to perform the physical-chemical and biological quality control of FDEs marketed in compounding pharmacies, evaluating the impact of the composition of the extracts on biological activities. The physical-chemical quality control was performed by means of the identification by thin layer chromatography (TLC), determination of the moisture by the volumetric method, total tannins content by a miniaturized spectrophotometric method, and contents of ellagic acid and punicalagin by high performance liquid chromatography with detection in the ultraviolet region (HPLC-UV). Biological quality control was performed with the in vivo evaluation of the anti-inflammatory activity (carrageenan-induced paw edema in mice), in vitro evaluation of antibacterial activity using broth microdilution and agar diffusion techniques and antioxidant activity by the method involving the reduction of thiazolyl tetrazolium blue bromide (MTT). The impact of FDEs on hemostasis was also evaluated by automated determination of activated partial thromboplastin time and prothrombin time in human plasma. The results obtained in the identification and determination of the total tannins and ellagic acid and punicalagin contents were consistent with each other and with the appearance of the FDEs, so that grey extracts have high levels of ellagic acid and low levels of punicalagin and total tannins, showing the characteristic spot of ellagic acid in the chromatographic plates. For these FDEs, good responses were not obtained in the assays for evaluation of antibacterial and antioxidant activities, contrary to the observed for the antiinflammatory activity. On the other hand, brown or yellow FDEs with high levels of punicalagin and total tannins, low levels of ellagic acid and characteristic spots of punicalagin on the chromatographic plates presented expressive antibacterial and antioxidant activity according to the performed tests. No impact on hemostasis was observed considering the dose usually recommended. In view of the results, it is evident the importance of the regulatory and supervisory agencies' actions on the production and commercialization of FDEs, being fundamental more rigour in the quality control of these products, in order to assure the therapeutic effect and the safety of the patient. Thus, it can be concluded that the work contributed both to national and global scientific enrichment and to public health.